Traditionally Important Herbaceous Medicinal Plants of Majathal Wildlife Sanctuary, District Solan, Himachal Pradesh, North Western Himalaya, India - Kumari, Krishna; Verma, Raj Kumar (Journal of Plant Resources, 2022)
The Himalayas is one of the mega diversity hotspots of the world, which contribute a great to the biodiversity wealth of the world. Among the biogeographic provinces of India, the Indian Himalayan Region (IHR) is well known for its diversity of ethnomedicinal plants. Majathal Wildlife Sanctuary is situated in District Solan, Himachal Pradesh, North Western Himalaya, India. In the present study, social surveys were conducted through the application of semi-structured questionnaire. All 39 villages inside and near the boundary (up to 2 km) were selected for the survey in the sanctuary. All the houses were surveyed and people of different ages and sexes were asked and their responses were recorded. A reconnaissance survey was conducted for the floristic diversity in the area and plant samples were collected for identification and herbarium preparation. In the sanctuary, there were 51 species of herbaceous medicinal plants identified which were used by local people. The results showed that the knowledge regarding medicinal plants was very less in the new generation as compared to the old age and middle age people. This study will help to know more medicinal plants from the villages and procure knowledge for future studies. This documented information will be preserved and utilized for mankind and make local communities economically stable and healthy.